Keterwakilan SDM Perempuan dalam Politik di Indonesia - Sitti Rakhman (Jurnal Deliberatif, 2023)
This study aims to find a contextual model of women's human resources in politics in Indonesia in order to achieve a representation of 30 (thirty) percent or more. The method of collecting primary and secondary data is by in-depth interviews with two key informants from election organizers, one FGD law, & documentation of the 2004 to 2019 election law. The data analysis method uses descriptive qualitative analysis with a combination of article analysis related to the representation of women in the election law from 2004 to 2019 using a feminist legal perspective. The results of the study show that the Conceptual model of representing women's human resources in politics in Indonesia needs to be affirmed through revisions to the election law and political parties changing the words "paying attention" or "considering" to the words "include or include" women accompanied by strict sanctions.